A Feasibility Study for Life Signs Monitoring via a Continuous-Wave Radar - Francesco Soldovieri; Ilaria Catapano; Lorenzo Crocco; Lesya N. Anishchenko; Sergey I. Ivashov (International Journal of Antennas and Propagation)
We present a feasibility study for life signs detection using a continuous-wave radar working in the band around 4 GHz. The data-processing is carried out by using two different data processing approaches, which are compared about the possibility to characterize the frequency behaviour of the breathing and heartbeat activity. The two approaches are used with the main aim to show the possibility of monitoring the vital signs activity in an accurate and reliable way.